LUGHAWI TAFSIR OF á¸¤Ä€SHIAH AL-á¹¢Ä€WI: A CRITICAL ANALYSIS OF TAFSÄªR AL-JALÄ€LAIN - Anwar, Rosihon (Al-Bayan: Jurnal Studi Ilmu Al- Qur'an dan Tafsir, 2020)
Various approaches are employed by exegetes to understand the Qurâ€™an. One of those approaches is the linguistic approach. One of tafsÄ«r utilises the linguistic approach is á¸¤Äshiahal-á¹¢ÄwÄ«Â 'AlÄ TafsÄ«r al-JalÄlain. This article investigates the characteristics and the unique attribution of á¸¤Äshiah al-á¹¢ÄwÄ«Â in its interpretation of the Qurâ€™an, especially in the language rules usage through his examples in explaining the verses. This study employs a qualitative method to the data gathered from literature (library research) descriptively. The Data analysis technique used the Seidel model through several stages of the process, namely identifying the results of data collection through data clarification, license, analysis, and data categorization. This research shows that á¸¤Äshiah al-á¹¢ÄwÄ«Â 'AlÄ TafsÄ«r al-JalÄlain is an essential and comprehensive interpretation using a linguistic approach. Al-á¹¢ÄwÄ« equipped his interpretation by explaining Nahwu (syntax), á¹¢araf (morphology), and the language rules application. He even quoting Alfiyyah Ibn MÄlik, complete with its syi'ir which are very rare to do by other commentators to make his tafsÄ«rÂ more comprehensive. Several characteristics in á¸¤Äshiah al-á¹¢ÄwÄ«Â used a linguistic approach to the Qurâ€™an utilizing the Arabic principle of mubtadi (basic), especially in the â€˜IrÄb (inflection) discussion. In this study, á¸¤Äshiah al-á¹¢ÄwÄ«Â 'AlÄ TafsÄ«rÂ al-JalÄlain can be categorized as an independent tafsÄ«rÂ that differ from tafsÄ«rÂ Al-JalÄlain. Al-al-á¹¢ÄwÄ«Â not only explaining in detailÂ tafsÄ«rÂ Jalalain but also criticizing and comparing it.